LANDMARKS OF ROMANIAN SOCIOLOGY –SOCIOLOGICAL INSTITUTE BANAT-CRIŞANA (PANGEEA, 2025)
The direct research of the reality of society, including social life frameworks and the interpretation of social facts, is treated as sociology. The paper adopts qualitative methods and document analysis, drawing on monographs and journals from the Banat-Crişana Social Institute to outline the institute's role, social problems, and the depopulation and development of Banat, including minorities, education, health, and social policy.
Keywords: Banat; interculturality; social life; minorities